2015
DOI: 10.17058/tecnolog.v19i1.4500
|View full text |Cite
|
Sign up to set email alerts
|

Características dimensionais e ponderais das semeadoras-adubadoras de precisão no Brasil

Abstract: ____________________________________________________________________________________________________________ RESUMOO objetivo do trabalho foi analisar as características dimensionais e ponderais das semeadoras-adubadoras de precisão fabricadas no Brasil. Para isso, foi realizado um levantamento de 20 dos principais atributos das máquinas, a fim de confeccionar um banco de dados organizados em uma planilha eletrônica, utilizando-se o software Microsoft Excel. Os resultados indicaram um total de 18 marcas, que e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…In a survey on the dimensional and ponderal characteristics of precision planters in Brazil, Francetto et al (2015) indicated that the fertilizer metering mechanisms used were the helical (94.4%), horizontal toothed rotor (2.9%), grooved rotor (2.2%), and horizontal toothed rotor (0.5%).…”
Section: Introductionmentioning
confidence: 99%
“…In a survey on the dimensional and ponderal characteristics of precision planters in Brazil, Francetto et al (2015) indicated that the fertilizer metering mechanisms used were the helical (94.4%), horizontal toothed rotor (2.9%), grooved rotor (2.2%), and horizontal toothed rotor (0.5%).…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors that can influence the longitudinal distribution of seeds in the soil, the sowing speed and the dosing system should be considered to obtain a stand with the highest number of adequate spacings between plants in the line. A survey conducted by FRANCETTO et al (2015) indicates that in Brazil, seeders use two main types of seed-dosing mechanisms, the horizontal disc and the tire, the first being used in approximately 79.57% of the machines and the second in 20.43%.…”
Section: Introductionmentioning
confidence: 99%
“…The correct dosage of fertilizers by the seed cum fertilizer drill is an essential step in the process of implanting any crop, contributing to its development and yield. Contextualizing this operation, in the Brazilian market, more than 94.4% of the seed drills are equipped with helical thread type fertilizer metering (Francetto et al, 2015). This mechanism is found in four models: helical by gravity, helical by lateral or longitudinal discharge through overflow, and two longitudinal helicoids.…”
Section: Introductionmentioning
confidence: 99%